Frontiers in Topical Photoprotection - Margaret Sullivan; Constancio Gonzalez Obezo; Zachary Lipsky; Abhishek Panchal; Jaide Jensen (Cosmetics, 2025)
This review synthesizes the latest research and developments to take into consideration for creating advanced sun protection products that meet evolving consumer demands. It examines the multifaceted effects of solar radiation (UVB, UVA, blue light, and infrared) on the skin, detailing cellular damage mechanisms, including DNA and RNA damage, and oxidative stress. It covers advancements in sunscreen formulation science, delivery systems, and UV filters. It delves into testing methodology advancements addressing in vivo limitations, new regulatory guidelines, and the integration of artificial intelligence from new UV filter development to consumer facing apps. Finally, it highlights biotechnology’s potential to deliver novel sustainable UV filters. By providing a holistic perspective on these interdisciplinary advancements, this review serves as background reading, informing future sunscreen development and fostering a comprehensive approach to photoprotection that address current and emerging challenges.